Analisis Kualitas Layanan Website Menggunakan Metode Webqual 4.0 Dan Interface Performance Analysis Pada Dinas Xyz - MaySarah, M; Saputra, Eki; Monalisa, Siti; Ahsyar, Tengku Khairil (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Nowadays technological advances have shown very rapid progress. One technology that is developing rapidly is information and communication technology. The current development of information and communication technology cannot be separated from the role of the internet. One of the most important applications of the internet is websites. Basically, achieving perfect website quality will encourage user satisfaction. Good website quality can of course be realized by displaying a website that meets the criteria of the WebQual 4.0 method as a measuring tool to achieve user satisfaction. Based on the background, research will be carried out to determine the level of service quality of the e-Filing website in applying the Webqual 4.0 and IPA methods. The aim of this research is to measure the quality of website services, group the attributes into three Webqual 4.0 variables using the IPA method and provide recommendations for improving the service quality of the XYZ Service Website on the attributes that are prioritized for improvement. This research was conducted at DLHK Pekanbaru for 30 days using interview, observation and documentation methods. The sample in this research was 100 website users. The results of this research are that in the usability quality, there are several menus with errors whose contents do not match the name of the menu. In terms of information quality dimensions, it was found that the website menu was not timely, and the website was rarely updated. In terms of service interaction quality dimensions, there is no comment column facility on the website. In terms of service interaction quality dimensions, there is no comment column facility on the website so that users cannot provide suggestions or opinions.